Efficiency of Commercial Banks in Indonesia After the Covid-19 Pandemic - Andriansyah, Fajar; Julia, Aan (Jurnal Keuangan dan Perbankan, 2023)
The impact of the Covid-19 pandemic has caused the condition of the banking sector, both conventional and sharia, in Indonesia to be unstable due to the policy of limiting the Covid-19 pandemic period which affects the efficiency of bank performance on credit and financing activities disbursed as well as bank operations. This research aims to measure the level of efficiency of Conventional Commercial Banks (CCB) and Sharia Commercial Banks (SCB) in Indonesia after the Covid-19 pandemic and to find out whether or not there is a difference in efficiency between CCB and SCB after the Covid-19 pandemic. The method used in this study is a quantitative method with a Data Envelopment Analysis (DEA) analysis model and a different test with the inputs used, namely capital, assets, deposits, and operational costs, then the output consists of credit and financing realization, as well as operating income. The results showed that CCB achieved an average efficiency level of 98.8 percent and SCB achieved an average efficiency level of 98.6 percent, which means that both banks have reached high efficiency levels after the Covid-19 pandemic. Then CCB and SCB experienced fluctuations that tended to be the same, so that the results of different tests showed a probability value of 0.9138 and greater than 0.05, then H0 was accepted which means that there is significantly no difference between the efficiency of CCB and SCB after the Covid-19 pandemic. DOI: 10.26905/jkdp.v27i4.9776